2014
DOI: 10.1002/jbm.a.35216
|View full text |Cite
|
Sign up to set email alerts
|

Collagen/hydroxyapatite scaffold enriched with polycaprolactone nanofibers, thrombocyte‐rich solution and mesenchymal stem cells promotes regeneration in large bone defect in vivo

Abstract: A three-dimensional scaffold of type I collagen and hydroxyapatite enriched with polycaprolactone nanofibers (Coll/HA/PCL), autologous mesenchymal stem cells (MSCs) in osteogenic media, and thrombocyte-rich solution (TRS) was an optimal implant for bone regeneration in vivo in white rabbits. Nanofibers optimized the viscoelastic properties of the Coll/HA scaffold for bone regeneration. MSCs and TRS in the composite scaffold improved bone regeneration. Three types of Coll/HA/PCL scaffold were prepared: an MSC-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2015
2015
2107
2107

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 50 publications
(114 reference statements)
3
43
0
Order By: Relevance
“…43 It has been previously shown that incorporation of micro-and nanofibers with scaffolds improves the scaffold strength and stiffness. 44,45 Similar to their finding, the presence of polymeric nanofibers between the ceramic layers improved the mechanical properties of the ceramic layers (strength close to 90 MPa, as opposed to the reported value of 60 MPa, see Fig. 7), which would be advantageous to bone tissue engineering.…”
supporting
confidence: 73%
“…43 It has been previously shown that incorporation of micro-and nanofibers with scaffolds improves the scaffold strength and stiffness. 44,45 Similar to their finding, the presence of polymeric nanofibers between the ceramic layers improved the mechanical properties of the ceramic layers (strength close to 90 MPa, as opposed to the reported value of 60 MPa, see Fig. 7), which would be advantageous to bone tissue engineering.…”
supporting
confidence: 73%
“…Prosecká et al showed that even human TRS promotes tissue regeneration in a rabbit model with a minimal immunological negative response. 58 This kind of result favors TRS for further preclinical and clinical studies.…”
Section: Absorbance (Au)mentioning
confidence: 91%
“…Alfa granules of platelets contain a wide range of growth factors, including PDGF, TGF-β, PDAF, VEGF, EGF, PDEGF, ECGF and IGF. 9 It has been reported that the use of platelets is beneficial for healing of bone, 10 cartilage, 11 tendon, 12 hernia 13 and skin 14 defects. One of the main advantages of using platelets as a source of growth factor is the possibility of autologous use, which reduces the immune reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of growth factor delivery improved the scaffold colonization both in vitro 48 and in vivo. 10 The importance of the adhesion of the platelets to the surface of fibers is mainly in their immobilization. The results of SEM and the release study showed that platelets delivered active molecules for several days.…”
mentioning
confidence: 99%